Socioemotional Skills Development in Highly Violent Contexts : Measurements and Impacts - Dinarte Diaz, Lelys Ileana (Washington, DC: World Bank, 2022)
Non-cognitive skills can determine socioeconomic success and the transmission of economic status across generations. Yet, evidence of cost-effective interventions that aim to develop these skills for at-risk youth living in highly violent contexts is still scarce. This paper experimentally studies the social-emotional learning and protection components of an After School Program (ASP) for teenagers in the most violent neighborhoods of El Salvador, Honduras, and Guatemala. By combining administrative records and data gathered on-site via computer from task-based games and AI-powered emotion detection algorithms, this paper measures the ASP's impacts on behavior, academic performance, and non-cognitive skills. To measure the learning component, 21 public schools were randomly assigned to extracurricular activities (Clubs), a psychology-based curriculum that aims to strengthen participants' character (Virtue), or a mindfulness and relaxation technique program (Mindful). To estimate the protection component, 8 schools were selected as pure controls with a propensity score approach. Results show that the net learning component improved behavior at school by 0.46 standard deviations and reduced a proxy for stress by 0.45 standard deviations relative to the Clubs only ASP. These results were driven by the Virtue curriculum. Although the protection component negatively impacts social-emotional skills, it is, on average, more effective for students with worse behavior at baseline, indicating that the ASP curriculum and the characteristics of the population served are key in designing policies aimed at improving students' behavior.